Effects of commercial energy drink consumption on athletic performance and body composition - Ballard, S. L.; Wellborn-Kim, J. J.; Clauson, K. A. (The Physician and Sportsmedicine, 2010)
Energy drinks are frequently marketed to individuals interested in athletics and an active lifestyle. From 2001 to 2008, estimates of energy drink use in adolescent to middle-aged populations ranged from 24% to 56%. Most energy drinks feature caffeine and a combination of other components, including taurine, sucrose, guarana, ginseng, niacin, pyridoxine, and cyanocobalamin. This article examines the evidence for 2 commonly purported uses of energy drinks: athletic performance enhancement and weight loss. Observed ergogenic benefits of energy drinks are likely attributable to caffeine and glucose content. There is conflicting evidence regarding the impact of energy drinks on weight loss, although some data suggest that combining energy drink use with exercise may enhance body fat reduction. As with any pharmacologically active substance, energy drinks are associated with adverse effects. Combining energy drinks with alcohol exacerbates safety concerns and is an increasingly common practice contributing to toxic jock identity among college-aged male athletes. Practitioners should monitor identified populations likely to consume these loosely regulated beverages